ความชุกของความเครียดจากการทำงานและปัจจัยทางจิตสังคมที่เกี่ยวข้องของคนงาน ส่วนการผลิตโรงงานอุตสาหกรรมแมกเนติกเทปและอัลคาไลน์แบตเตอรี่แห่งหนึ่ง - วรินทร์ บุญเลี่ยม (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objectives were to study the prevalence and the related psychosocial factors of occupational stress among the workers in the production department of a magnetic tape and alkaline battery industry. The population samples were 359 workers, 87 males and 272 females, aged 17 to 38 years (mean aged 25.6). The study was conducted during March and April 2000. Self administered questionnaire was consisted of questionnaire adapted from Cooper and Davidson model of occupational stress, the General Health Questionnaire-12(GHQ-12), Thai version, the Jalowiec Coping Scale and the Impulsiveness-Venturesomeness-Empathy Inventory (IVE inventory) developed by Eysenck and McGurk. The results were 1) The prevalence of the occupational stress was 56.1 percents (95% Cl:50.8-61.2) 2) The psychosocial factors and occupational stress were found to be significantly related (P<0.05, by Chi-square tests). In the individual arena, age was critical factor. In the work arena ; relation with co-workers, problems at work, activity participation, high temperature environment, sufficient performances, self-esteem, job security, satisfied with salary, non-monetary rewards, precise job descriptions, consultation with heads, were major factors. In the home arena ; warmth in the family, adequate housing, family disputes e.g. financial and children, individual incomes, total family incomes, financial status, exercise and quality of sleep, were important factors. 3) The stress experienced workers preferred to use the emotive coping, the evasive coping and the fatalistic coping styles than the confrontive coping style. 4) Finding for the personality trait:the stress experienced female workers showed more impulsiveness than the non-stress female workers. The results of this study should be beneficially considered in primary prevention program to reduce or eliminate stressors and improving the adequate coping styles of the operation workers.